Silver Diamine Fluoride Staining With Potassium Iodide: A Prospective Cohort Study - Jilen Patel; Bathsheba Turton; Sarah Cherian; Robert Anthonappa (International Dental Journal, 2024)
ABSTRACT: Background: Staining after silver diamine fluoride (SDF) treatment limits treatment acceptability but is also used as a clinical indicator of lesion stability. Potassium iodide (KI) has been postulated to modify SDF staining. Understanding the natural history and resultant shade of SDF/KI-treated lesions will inform clinical decision-making. This study describes the change in colour of carious lesions in primary teeth treated with SDF and KI. Methods: One hundred carious lesions in primary teeth were treated with SDF + KI (Riva Star, SDI) and followed up over 6 months. Lesion shade was determined using standardised intraoral photography and broadly categorised into 4 shades: yellow, light brown, dark brown, and black. Lesions were digitally isolated, and colour was evaluated using CIELAB (L*: lightness, a*/b*: hue) and perceptible colour change (ΔE). Results: One hundred valid observations were analysed on 129 lesions included in the study. Lesions were excluded if subsequently restored (n = 15), teeth exfoliated (n = 2), exhibited pulpal exposure (n = 1), or failed to attend at follow-up visits (n = 11). At baseline, the shade of carious lesions was yellow (n = 22), light brown (n = 19), dark brown (n = 29), or black (n = 30). The changes in shade between baseline and 6 months were clinically perceptible to the human eye, with the mean ΔE being 12.2 (SD = 6.9). Neither tooth type, lesion severity, nor baseline shade was statistically associated with the degree of perceptible change at 6 months. Conclusions: Carious lesions exhibited clinically significant changes in colour after application of SDF + KI, primarily attributed to differences in L* of lesions over the 6 months.